2023
DOI: 10.1128/mbio.02686-22
|View full text |Cite
|
Sign up to set email alerts
|

How Epstein-Barr Virus Induces the Reorganization of Cellular Chromatin

Abstract: Five families of viruses support the reorganization of cellular chromatin (ROCC), the compaction and margination of host chromatin, upon their productive infection. That they all share this phenotype implies the importance of ROCC in viral life cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Recent studies examining EBV's role in the reorganization of cellular chromatin (ROCC) using single‐gene knock out EBV library demonstrated that each of EBV's seven core lytic DNA synthesis genes (BALF5, BALF2, BBLF2/3, BBLF4, BSLF1, BMLF1, and BMRF1) and its origin of lytic replication (oriLyt) are required for ROCC. Further examining BALF5's role in ROCC showed that exogenously introduce wild‐type BALF5 instead of D755N/D757N, Y753F, and S758T mutant BALF5 into 293/EBV ΔBALF5 cell line supports ROCC 83 . BZLF1, is an EBV‐encoded immediate early gene that drives EBV switch from latency to lytic replication.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent studies examining EBV's role in the reorganization of cellular chromatin (ROCC) using single‐gene knock out EBV library demonstrated that each of EBV's seven core lytic DNA synthesis genes (BALF5, BALF2, BBLF2/3, BBLF4, BSLF1, BMLF1, and BMRF1) and its origin of lytic replication (oriLyt) are required for ROCC. Further examining BALF5's role in ROCC showed that exogenously introduce wild‐type BALF5 instead of D755N/D757N, Y753F, and S758T mutant BALF5 into 293/EBV ΔBALF5 cell line supports ROCC 83 . BZLF1, is an EBV‐encoded immediate early gene that drives EBV switch from latency to lytic replication.…”
Section: Introductionmentioning
confidence: 93%
“…Required for reorganization of cellular chromatin 83 Viral DNA synthesis affects global chromatin compaction BZLF1 Open up both host and EBV chromatin during lytic replication 84,85 ATPase INO80 84 and EBNA3C bind to the MTAP gene body upstream of CCND2A/B loci, and RNAPII ChIA-PET connects the CDKN2A/B loci to the MTAP promoter. Using 3 C assay, we confirmed that the inactivation of EBNA3A or 3 C decreases the promoter interactions among p14 ARF , p15 INK4B , and p16 INK4A .…”
Section: Ebna3a/c In Host Cellular Genome Organizationmentioning
confidence: 99%
“…In EBV this change is mediated by SM (also known as Mta or EB2) and appears to be important for both export of viral mRNAs and their translation [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Progression of the lytic cascade is accompanied by such extensive compaction and margination of host chromatin that further host transcription becomes untenable [ 64 , 65 ]. These additional mechanisms may contribute to the ability of herpesviruses to usurp their host’s translational machinery.…”
Section: Non-hsf Viral Proteins Contribute To Impaired Host Gene Expr...mentioning
confidence: 99%
“…A specific phenotype of virus-induced ROCC is observed in 2 of the families but is likely to be generally required by all 5 virus families. Both geminiviruses and herpesviruses seem to condense cellular DNA prior to margination [ 7 , 19 ]. Geminiviral infection of tobacco cells leads to extensive condensation of cellular DNA, rendering it akin to “prophase-like fibers,” which are likely precursors to the compaction of host chromatin and its movement to the nuclear periphery [ 19 ].…”
Section: What Does Virus-induced Rocc Look Like?mentioning
confidence: 99%
“…Geminiviral infection of tobacco cells leads to extensive condensation of cellular DNA, rendering it akin to “prophase-like fibers,” which are likely precursors to the compaction of host chromatin and its movement to the nuclear periphery [ 19 ]. Similarly, blocking extensive viral DNA synthesis in EBV-infected cells induced to enter their productive phase supports the condensation of cellular DNA, but not its margination [ 7 ]. It thus seems likely that the condensation of cellular chromatin precedes its margination.…”
Section: What Does Virus-induced Rocc Look Like?mentioning
confidence: 99%